THE UNDERSTANDING VILLAGE COMMUNITY OF KOTO SENTAJO TOWARDS THE EXISTENCE OF SENTAJO RAYA PROTECTED FOREST KUANTAN SINGINGI REGENCY PROVINCE OF RIAU - Erpino; Evi Sribudiani; Defri Yoza (Jurnal Ilmu Ilmu Kehutanan, 2019)
Sentajo Raya Protection Forest is one of the protected forest areas in Riau Province, right in Kuantan Singingi Regency. The existence of Sentajo Raya Protected Forests has benefits for communities around the area, where timber forest products can be utilized, used as educational forests, and used as tourist attractions. To maintain forest preservation, the community replanted inside the area after logging. The purpose of this research was to find out the understanding, the response of Koto Sentajo village community and the forms of disturbances in Sentajo Raya Protection Forest. This research method uses random sampling, Determination of the number of respondent in this research using Slovin formula. Primary data collection techniques through interviews and observations. Secondary data collection techniques through collection of library materials that can support primary data collection. The results showed that the understanding and response of the people of Koto Sentajo village was relatively good, with each percentage of the community's answers being 96.25% and 95.00%. The form of disturbance found in Sentajo Raya Protection Forest was in the form of taking wood in small quantities.